Maternal and Fetal Outcomes of Pregnancies in Wilson’s Disease: A Single-Centre Real-Life Experience - Demir, Kadir; Çifcibaşı Örmeci, Aslı; Çavuş, Bilger; İstemihan, Zülal and Genç, Sezen and Atasoy, Alp and Akyüz, Filiz and Beşışık, Fatih and Kaymakoğlu, Sabahattin (Turkish Journal of Gastroenterology, 2025)
Background/Aims: This study aims to investigate the fetal outcomes and pregnancy course in patients with Wilson’s disease (WD). Materials and Methods: A total of 54 female patients with a diagnosis of WD and a history of pregnancy between 1985 and 2021 were retrospectively examined in a specifically WD outpatient clinic in the İstanbul Faculty of Medicine. Results: A total of 131 pregnancies in 54 patients were examined. The mean age at diagnosis of WD was 22.1 ± 10.8 years. The mean follow-up period of patients diagnosed with WD was 87 ± 80 months. Forty (74.1%) patients were diagnosed with hepatic, 5 (9.3%) neurological, and 9 (16.6%) with mixed involvement WD. The liver was cirrhotic in 68 (51.9%) pregnancies. Ninety-eight (74.8%) preg nancies resulted in live birth, 30 spontaneous abortions (22.9%), and 3 (2.3%) stillbirths. Pregnancies diagnosed with mixed pattern WD had a lower live birth rate than those diagnosed with WD with isolated hepatic or neurological involvement (P < .001 and P = .004, respectively). While the spontaneous abortion rate decreases with WD treatment, the rate of live birth, stillbirth, premature birth, and low birth weight did not change in the total group. During pregnancy, patients used D-penicillamine, trientine, and/or zinc. Conclusion: With careful monitoring and management by medical professionals, pregnant women diagnosed with WD can still achieve successful pregnancies and improve their quality of life. Cite this article as: Demir K, Örmeci AÇ, Çavuş B, et al. Maternal and fetal outcomes of pregnancies in Wilson’s disease: A single centre real-life experience. Turk J Gastroenterol. Published online October 22, 2025. doi:10.5152/tjg.2025.25448.